Pearson nurse's drug guide 2012 - Wilson, Billie Ann; Shannon, Margaret T.; Shields, Kelly M. (Pearson, 2012)
Features of this book include: clearly identified IV preparation and administration, including push, continuous, or intermittent; explanation of clinically relevant drug interactions with food, herbals, and other drugs; pharmacological classifications paired with therapeutic classifications for every drug monograph for ease of use by clinicians and students; dosages across the life span with adjustments for clinically relevant conditions; glossary of clinical conditions and their related signs and symptoms; and prototype drugs.--From cover, p. [4]